The Effect of Dysmenorrhea Exercise on Reducing Dysmenorrhea in Grade X Adolescent Females - Nyoman, Ni Nyoman Sukmawati; Puspita H, Richta; Yuliana, Dewi (Global Indonesia Health Care (GOICARE), 2025)
Background: Dysmenorrhea is a prevalent menstrual disorder among adolescent females, often associated with significant discomfort and disruption of daily activities. In Indonesia, it represents one of the most common menstrual complaints in adolescents. Non-pharmacological interventions such as dysmenorrhea exercise, have been proposed as accessible and low-cost approaches to alleviate menstrual pain. Purpose: This study aimed to assess the effect of dysmenorrhea exercise on reducing pain intensity among female adolescents in grade X at SMAN 1 Seputih Raman, Indonesia. Methods: A pre-experimental one-group pre-test and post-test design was employed. A total of 66 female students were selected using accidental sampling. Dysmenorrhea pain levels were assessed using the Numeric Rating Scale (NRS), and data were collected via observation sheets. The Wilcoxon signed-rank test was used to analyse changes in pain levels before and after the exercise intervention. Results: The results showed a statistically significant reduction in dysmenorrhea pain following the exercise intervention, with a p-value of 0.000 (p < 0.05). This finding supports the hypothesis that dysmenorrhea exercise can effectively decrease the severity of menstrual pain in adolescent girls. Conclusion: Dysmenorrhea exercise appears to be a beneficial, non-invasive intervention to manage menstrual pain in adolescents. These findings suggest that regular implementation of such exercises could serve as a practical strategy for pain relief and health promotion among school-aged females. Further studies with control groups and long-term follow-up are recommended to confirm and expand upon these results.